PRESENCE OF LACTOSE IN MEDICATIONS FOR THE TREATMENT OF HYPERTENSION - Dias, Alexandra Pimenta de Almeida; Peixoto, Lucca Kayan Silva; Oliveira, Leandra de Almeida Ribeiro; de Sousa, Letícia Cristina Alves; Oliveira, Pamela Cristina de Sousa Guardiano Reis; Oliveira, Pedro Alexandre Sampaio; de Oliveira Netto, Idari Francisco; Barbosa, Daniela Borges Marquez (Seven Editora, 2026)
Introduction: Medications used to treat hypertension in the Brazilian population, containing lactose as an excipient in solid pharmaceutical form, cause undesirable effects in patients with lactose intolerance. Objective: To ascertain the presence of lactose as an excipient in medications in solid pharmaceutical form available on the market that are used to treat hypertensive patients. Methodology: To evaluate the medications present in the National List of Essential Medicines (Rename), indicated for the treatment of hypertension or comorbidities that may occur alongside hypertension. Generic, similar, and reference medications were selected from the market to evaluate the drug information and determine the presence or absence of lactose. Results: Of the 151 medications analyzed and grouped according to pharmaceutical forms, therapeutic classes, brands, and categories, data regarding the presence of lactose were collected from the electronic drug information database of the National Health Surveillance Agency (ANVISA) and from pharmaceutical industry websites. It was detected that lactose is present in 60.93% of the selected medications, being more frequent in tablets (60.87%) and coated tablets (39.13%), and no lactose was found in dragees, respectively. It was predominantly found in reference medications (47.83%), followed by generics (31.52%), and similar medications presented a proportion of 20.65%. Conclusion: Lactose is one of the most used excipients in solid medications, as it provides greater resistance to the form. 60.93% of the analyzed medications contain lactose in their formulation; therefore, it is essential to include a warning phrase on medication boxes due to the risk posed to people with lactose intolerance.